1990
DOI: 10.2307/1938295
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Population Fluctuations in Larval and Adult Stages of the Wood Frog (Rana Sylvatica)

Abstract: During a 7—yr population on the wood frog, Rana sylvatica, the breeding population size fluctuated by a factor of 10 and juvenile production by a factor of 100. Variation in the adult population among years was largely due to variation in juvenile recruitment. Annual net replacement rates (Ro) varied from 0.009 to 7.49. Survivorship curves (calculated using the number of eggs deposited as the initial point) showed that most variation in the proportion of individuals surviving to adulthood was due to variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
701
3
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 729 publications
(734 citation statements)
references
References 30 publications
22
701
3
8
Order By: Relevance
“…The most pervasive sublethal effects of Hg we observed were reductions in larval and juvenile body size. Because smaller size at metamorphosis can delay maturation (Berven 1990, Scott 1994, we incorporated this sublethal effect by reducing the proportion of female B. americanus that matured at age three vs. age four. Somewhat surprisingly, we found that delaying maturation by up to one year had little effect on adult population size or extinction probability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most pervasive sublethal effects of Hg we observed were reductions in larval and juvenile body size. Because smaller size at metamorphosis can delay maturation (Berven 1990, Scott 1994, we incorporated this sublethal effect by reducing the proportion of female B. americanus that matured at age three vs. age four. Somewhat surprisingly, we found that delaying maturation by up to one year had little effect on adult population size or extinction probability.…”
Section: Discussionmentioning
confidence: 99%
“…For each scenario, we adjusted survival parameters based on all observed effects of Hg on survival or embryonic viability (Table 1). Because the most pervasive sublethal Hg effects we observed were reductions in larval and juvenile body size, and because smaller size at metamorphosis can delay maturation (Berven 1990, Scott 1994, we incorporated this sublethal effect by reducing the proportion of female B. americanus that matured at age three vs. age four (q) by the observed reduction in growth rate. For these initial simulations, we assumed that sublethal reductions in body size had no positive or negative effect on other post-metamorphic individuals in the population.…”
Section: Evaluating Effects Of Maternally Transferred and Dietary Hg mentioning
confidence: 99%
“…Previous studies have shown that larval growth and development rates are correlated with components of adult fitness (Smith 1987;Semlitsch et al 1988;Berven 1990) and are important demographic factors in influencing overall population growth rate (Govindarajulu et al 2005). For other ranid frogs, the larval growth environment has been shown to influence postmetamorphic chance of survival, and time to sexual maturity (Altwegg and Reyer 2003).…”
Section: Conclusion From Tadpole Experimentsmentioning
confidence: 99%
“…Egg size and larval body size in amphibians are likely important components of fitness because they are positively correlated with size at metamorphosis (Berven 1990;Scott 1994), which in turn correlates positively with the probability of further survival (Altwegg and Reyer 2002), size at maturity (Smith 1987), and fecundity (Semlitsch et al 1988), although the opposite pattern, in which a small egg size confers a survival advantage, has also been reported (Kaplan and Phillips 2006). In the cannibalistic salamanders Hynobius retardatus (Michimae 2007) and Ambystoma opacum (Scott 1990), the potential for size-dependent cannibalism may be greatly increased by variation in the initial larval body size.…”
Section: Population Differences In Egg Sizementioning
confidence: 99%